2021
DOI: 10.3390/su132212451
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Sustainable Shopping Practices for Small Business during COVID-19

Abstract: The purpose of this study was to understand the factors that attract consumers to small businesses during the COVID-19 pandemic to assist with small businesses. Factors of interest included emotional (positive and negative) and cognitive experiences (resilience, optimism) during the pandemic and demographic characteristics (gender, generation, education, income, and employment status). Using a convenience survey sample in U.S. (N = 315), this study found that positive and negative emotions, active resilience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 78 publications
0
13
0
2
Order By: Relevance
“…These authors highlighted the potential of bringing these spaces online to contribute to sustainability in the face of system shocks such as during the covid-19 pandemic. Ha et al (2021) found that consumers who were resilient during the pandemic, that is, were able to recover quickly after a crisis, were more likely to patronize small businesses, thus contributing to their survival.…”
Section: Sustainability Of Consumption and Current Business Models (T...mentioning
confidence: 99%
See 2 more Smart Citations
“…These authors highlighted the potential of bringing these spaces online to contribute to sustainability in the face of system shocks such as during the covid-19 pandemic. Ha et al (2021) found that consumers who were resilient during the pandemic, that is, were able to recover quickly after a crisis, were more likely to patronize small businesses, thus contributing to their survival.…”
Section: Sustainability Of Consumption and Current Business Models (T...mentioning
confidence: 99%
“…The pandemic brought as a consequence a change in the priorities of consumers, generating new purchasing behaviors to cope with the uncertainty of the pandemic, demonstrating greater concern for the social and ecological, and supporting efforts to achieve sustainability and well-being of the society in this new economic environment (Sharma et al, 2021). As covid-19 spread throughout the world, consumers faced major changes in their daily activities, including the closure of many businesses that did not know how to adapt, while those that did experience supply chain disruptions were influenced by product availability (Ha et al, 2021). In this context, people spent much more time in their homes, so they had to adopt different technologies to make purchases, and they were much more aware of the importance of saving water and energy, which has generated greater awareness of waste, as well as the adoption of some pro-environmental and social practices (Arias et al, 2021).…”
Section: Sustainability Of Consumption and Current Business Models (T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiencia disfrutable (Esposti, Mortara, y Roberti, 2021;Matacena et al, 2021;Qi et al, 2020) Emociones (Alsetoohy, Ayoun, y Abou-Kamar, 2021;Ha, Childs, Sneed, y Berry, 2021;Li et al, 2021) Confianza (Cachero-Martínez, 2020;Czeczotko et al, 2021;Skalkos et al, 2021) Valores del consumidor…”
Section: Estado Emocionalunclassified
“…Las emociones fueron un factor relevante en el consumo alimentario sustentable, pues el estado de ánimo fue un factor que incidió en el consumo de alimentos con atributos sustentables (Li et al, 2021). El grado en que los consumidores experimentan emociones y la resiliencia durante la pandemia influyeron en su frecuencia de compra sustentable (Ha et al, 2021).…”
Section: Estado Emocionalunclassified